Incidência, prevalência e severidade de problemas de saúde e valores de referência para testes de desempenho físico em judocas adolescentes - Fernanda Oliveira Madaleno (2020)
Judo is martial art and Olympic sport where the physical and physiological differences between sexes may contribute to different incidence, prevalence, and profile of injuries between female and male youth judokas. In addition, youth judokas are engaged in high-intensity efforts of intermittent nature that require strength and range of motion (ROM) of different muscles and joints. With this, the studies presented in this dissertation aimed to provide reference values of physical performance tests in youth judo athletes and compare the prevalence, severity and profile of health problems, in addition. The first study provide reference values for handgrip strength, shoulder and ankle range of motion (ROM) and upper-limb and lower limb stability for youth judokas of both sexes and investigate the effects of sex and side dominance. A total of youth judokas from under-18 (n=60) and under-21 (n=77) categories of both sexes were assessed. Handgrip strength was assessed using a Jamar dynamometer, ankle ROM was measured by lunge test, shoulder ROM was assessed by an inclinometer and upper-limb and lower limb stability were assessed by the Closed Kinetic Chain Upper Extremity Stability Test (CKCUEST) and by the Modified Star Excursion Balance Test (mSEBT). In both categories, males had greater handgrip strength. In the under-18 category, the dominant side had greater handgrip strength and the non-dominant side of females had smaller shoulder external rotation ROM than the dominant side and also than both sides of males. In addition, females had greater shoulder internal rotation ROM. In the under-21 category, the dominant side of females had greater ankle dorsiflexion ROM than the dominant side of males and males had better performance in the mSEBT. The second study compare the incidence, prevalence, severity and profile of injuries (sudden and gradual onset) and illness between youth female and youth male judokas. Specifically, 154 youth judokas (83 males and 71 females) completed the Oslo Sports Trauma Research Center questionnaire on health problems (OSTRC-H) questionnaire during 30 weeks. The OSTRC-H was distributed weekly among the judokas through the Google form platform, starting in the first week of the sports preseason. The incidence, prevalence, and severity of illnesses and sudden and gradual onset injuries were compared between sexes using independent t-test (variables with normal distribution) or Mann Whitney U test (variables with non-normal distribution) with α set a 0.05. Female and male judokas showed 16.96 and 16.57 injuries per 1000 athletic-exposures, respectively (p=0.383). For average weekly prevalence of health problems, females judokas (38.35%) showed higher values than youth males judokas (29.82%). In addition, females had greater prevalence of injuries (p<0.001) and gradual onset injuries (p<0.001) than males. In the severity of the injuries, there was no statistical difference between the sexes. The findings of both studies demonstrated that there are differences for prevalence of health problems and for variables of muscle strength, ROM and lower limb stability between female and male youth judokas. Thus, these data can provide guidance in the development and implementation of injuries prevention programs for youth judokas, considering the difference between sexes, in addition to guide assessment of youth judokas screening during the sports preseason.